ANALYSIS OF LAWN QUALITY AND STATUS OF DIARRHEA DISEASE IN PANTON MAKMUR VILLAGE, KRUENG SABEE DISTRICT, ACEH JAYA DISTRICT YEAR 2023 - Karma, Taufiq; Hidayatullah, Mhd.; Oriza, Mutia (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
Diarrhea remains a significant health issue in developing countries, including Indonesia. In August 2023, data from the Ministry of Health reported an incidence of 189,215 diarrhea cases across Indonesia. In Aceh Jaya Regency, 151 cases were identified, with the Calang Community Health Center recording 151 cases and Panton Makmur Village reporting 15 cases. This research aimed to assess latrine availability, latrine quality, and the incidence of diarrhea in Panton Makmur Village. The study employed an analytical descriptive observational approach using secondary data. The research subjects were mothers, with a population of 286 households, and a sample of 15 individuals was drawn from the secondary data. The findings indicate a relationship between latrine ownership and the incidence of diarrhea, as well as a relationship between latrine quality and the incidence of diarrhea.